The Relationship between Spirituality and Theology - Callahan, Annice (Horizons, 1989)
This essay considers the contribution which spirituality makes to theology and vice versa, using examples from Karl Rahner's work. His spirituality in the sense of lived religious experience is the point of departure for his theological anthropology. Conversely, his theology of devotion to the Sacred Heart critiques and informs a spirituality of the heart of Christ. After discussing the mutual benefits which spirituality and theology provide one another, this paper points out the contemporary relevance of a spirituality of Christ's heart.